നാലുകെട്ട് | Naalukettu - M.T. Vasudevan Nair (Current Books, 1958)
Novel by M T Vasudevan Nair with illustrations by Artist Namboodiri. M T Vasudevan Nair delineate the lives of individuals struggling to negotiate disintegrating feudal structures and values. Naalukettu tells the story of a young boy, Appunni, against the history of his tharavadu, a matrilineal joint family. This novel won the author Kerala Sahithya Akademi Award in 1959.